A measurement method of fifth-generation multiple-input multiple-output antenna based on microwave imaging - Hangyu Chen; Jingcheng Zhao; Tao Hong; Shuli Zheng; Haohui Hong; Mohamed Cheriet (International Journal of Distributed Sensor Networks)
An increase in the quantity and density of antenna elements increases the mismatched failure rate and measurement difficulty of the multiple-input multiple-output. To simplify the measurement method of the S 11 parameter utilizing the traditional vector network analyzer, this article proposes a multiple-input multiple-output measurement method based on microwave imaging. The multiple-input multiple-output element was designed, and then the existence of mismatched scattering of the mismatched state through microwave one-dimensional and two-dimensional imaging simulations was verified. A wideband Vivaldi antenna was designed for measurement imaging verification. The research results show that the proposed method is capable of detecting the mismatched scattering of mismatched elements as well as accurately locating the mismatched elements and mismatched position of circuits behind the element, which improves the measurement efficiency.